La nouvelle histoire et Lévi-Strauss - Richard Marin (Caravelle)
During the 1970’s the French movement known as New History innovated in this field by the choice of new subjects –death, fear, love, family … - which up to then were dealt with by anthropology. As a result, the question of the connection with the discipline ruled by Lévi-Strauss rose with new acuteness. Therefore, this article aims to analyze the relationship between this history dealing with mentalities and anthropology, and more especially with the one practised by the author of Tristes Tropiques.